(untitled) (Texas Journal of Engineering and Technology, 2023)
This article reveals international harmony is acting as a factor of self-determination of nations, non-discrimination of other nations, social development and equal rights of nations. In all spheres of science, education and production, mutual cooperation activities of representatives of different nationalities are being organized